Analisis Kontribusi Pajak Daerah dan Retribusi Daerah terhadap Pendapatan Asli Daerah di Kabupaten Maluku Tenggara - Gomies, Stevanus J.; Pattiasina, Victor (STIE Widya Manggala, 2011)
The study identified that with the model used, it can be used to view the local tax contribution and regional retribution against the original Revenue areas. Based on the results of statistical tests, then it can be inferred that the model used to measure the local tax levy and the original revenue is able to explain variations of the region. This can be seen, if there is a 1 percent increase in the tax levy and the original revenue can increase the area that each of 0,249 and 0.505 percent. On the other hand R (coefficient of determination) indicates the number of 3.139 percent identified that the magnitude ofthe influence of the variable X to variable Y of 81,7 percent and the rest of 12.3 per cent determined by other variables that are not identified in this model. Economic implications that could be drawn from the test results above, is a donation or contribution/share local tax levy and the area has a strategic position in Enhancing support of The original revenue (PAD). Thus an attempt to improve the reception of the original revenue areas continue to do with intensification of efforts and extensification. Intensification of efforts can be done through improving the quality of human resources, quality of service and improved surveillance of the taxpayer effective. While the exstenfication collection was done by logging the object and the subject of taxes, the excavation of new sources and the creation of regional regulations more in line with the development of the State.